Desenvolvimento de forma farmacêutica líquida de micofenolato de mofetila para administração através de sondas - Lopes Filho, Flávio Rodrigues (2023)
Currently, the administration of drugs through tubes still requires improvements, due to the lack of scientific studies that demonstrate the safety and efficacy of using drugs through this route, with a frequent challenge related to the lack of standardized pharmaceutical forms compatible with this administration. The immunosuppressant mycophenolate mofetil (MMF) is mainly used in post-liver and kidney transplant therapies, but the liquid pharmaceutical form of this drug is not sold in Brazil. Considering the need to obtain stable and safe formulations to perform administration by this route, the objective of this work was to develop a suspension for administration in tubes containing mycophenolate mofetil. Initially, the identification was performed by High Performance Liquid Chromatography (HPLC) using the powder obtained from the tablets, in comparison with the reference chemical substance (SQR), together with the validation of the mobile phase chosen for the progress of the study. Subsequently, the critical process parameters (PCP) of the analytical method were evaluated, such as precision, accuracy, linearity, selectivity, limit of detection and quantification. The vehicle named “GUTE” used to prepare the suspension was evaluated for its pH and electrolyte addition and how they would affect the rheological behavior. For the preparation of the suspensions, the average weight of the tablets was evaluated, after which they were crushed and stirred in the vehicle. With the suspensions formed, assays of organoleptic characteristics, dosage, viscosity, pH, density and microscopy were carried out, accompanying the suspensions at room temperature (up to 25ºC) for 70 days and at refrigerated temperature (2 to 8ºC) for 63 days. The samples presented physical-chemical stability of the parameters of pH, density and viscosity, mainly, the refrigerated sample. The drug content obtained a result equal to 83.1% of the sample after 28 days stored at room temperature, while at refrigerated temperature it presented 86.46% after 63 days. In an experimental evaluation of passing the suspension through a nasoenteral (NET) and nasogastric tube, the suspension obtained greater drug recovery after administration through the NET. The results of degradation kinetics before the suspension for the content and viscosity by calculation of order two, the validity period was equal to 26 days of stability at room temperature, being fully possible its hospital use.